Pendidikan Kristen sebagai Solusi Progresif dalam Menanggapi Tantangan Kesenjangan Sosial - Sianturi, Novita; Wagiu, Meily M.; Manua, Englin R.; Veronika, Thelma; Solang, Zefanya (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
This article discusses the proactive movement of Christian religious education in responding to social inequalities. Christian religious education has the potential to transform the attitudes and behaviors of individuals and communities, motivating them to actively combat social injustice. Through the teaching of Christian values such as love, justice, and solidarity, Christian religious education can build strong social awareness and encourage concrete actions to address social disparities. This research employs a qualitative literature review aimed at elucidating the progressive proactive stance of Christian religious education in responding to the challenges of social inequality. The discussion yields several opportunities for Christian religious education in addressing social disparities: sensitivity to social issues, fostering inclusivity, empowering individuals in need, and engaging in dialectics.